Religious-cultural psychotherapy in the management of anxiety patients - Mohd Razali, Salleh; Kassim, Aminah; Khan, Umeed Ali (Sage, 2002)
This study investigated the effectiveness of incorporating sociocultural and religious aspects in the management of anxiety among Muslim patients of ethnic Malay origin. Eighty-five religious and 80 non-religious patients with generalized anxiety disorder (GAD) were randomly assigned to the study or control group. Both groups received a standard treatment for GAD, although the study group received additional religious–cultural psychotherapy (RCP). Patients were followed up and assessed periodically for six months. Religious patients receiving RCP showed significantly more rapid improvement in anxiety symptoms than those in the control group. The difference, however, became non-significant at the end of six months. There was no significant difference in improvement between the study and control group of non-religious patients. We concluded that RCP rapidly improved anxiety symptoms in Muslim patients with a strong religious background.